A Mechanism to Regulate Sovereign Debt Restructuring in the Euro Area - Jochen Andritzky; Désirée I. Christofzik; Lars P. Feld; Uwe Scheuering (Center for Economic Studies and ifo Institute (CESifo), 2016)
To make the no-bailout clause credible and enhance the effectiveness of crisis assistance, a consistent institutional and legal framework is needed to ensure that private creditors contribute to crisis resolution. Getting activated as part of ESM crisis assistance, we propose a two-stage mechanism that allows to postpone the fateful distinction between liquidity and solvency crises: At the onset of a ESM programme, the framework demands an immediate maturity extension if the debt burden is high, followed by deeper debt restructuring if post-crises debt proves unsustainable. The mechanism is easily implemented by amending ESM guidelines and compelling countries to issue debt with Creditor Participation Clauses (CPCs). As debt is rolled over, the mechanism gradually phases in, leaving countries time to reduce debt. Given that private sector in-volvement reduces financing needs, the ESM could provide longer programmes and more time for reforms.
Keywords: E62; F36; H63; 330; sovereign debt restructuring mechanism; no-bailout clause; creditor participation clauses; ESM